Stage Music and Paul Claudel’s Dramatic Strategy for ‘The Tidings Brought To Mary’. 1929–1932 Mystery Play Project (Global Journal of Human-Social Science, 2023)
This article looks at the system of theater and dramaturgy strategies devised by Paul Claudel to ensure interaction between elements of scenic speech and excerpts from stage music by Darius Milhaud in the context of the 1929 1932 project The tidings brought to Mary mystery play The methodology used in this research is relevant for interdisciplinary studies in humanities Aspects of Art History Cultural Studies philology and Dramatic Art combined shape new knowledge about Paul Claudel s theater and drama strategies in terms of scenic speech as well as the functions of stage music in the th century mystery play
Keywords: claudel; milhaud; mystery play; theater